(untitled) (Bangladesh Journal of Dental Research & Education, 2013)
Diagnosis of pulp status is an important clinical step to achieve success in pulp therapy technique or endodontic treatment in children. In pediatric dentistry, history of symptoms given by a child may not be reliable. Assessment of dental pulp status plays an important role. It is hoped that these guidelines will facilitate pulpal diagnosis, good decision-making and evidence-based practice for pediatric patients. DOI: http://doi.dx.org/10.3329/bjdre.v2i2.16248 Bangladesh Journal of Dental Research & Education Vol.2(2) 2012: 66-68